PENGEMBANGAN KEWIRAUSAHAAN DAN EKONOMI KREATIF DI MADRASAH - Muhammad Nur; Anisaurrohmah Anisaurrohmah (Cross-border, 2022)
In building the future of special madrasas through entrepreneurship, communicative attitudes are needed including being a good listener and energetic, not solely profit-oriented, having integrity, being aggressive, competitive, adventurous, perfectionist, cooperative, imaginative, being a pleasant person, being honest, change oriented, disciplined so that they can control themselves, visionary, become change managers, and want to excel, organizers, hard workers who have strong motivation, are committed, enthusiastic, negotiative and are able to market services/products.